Precursor-directed biosynthesis of catechol compounds in Acinetobacter bouvetii DSM 14964. Issue 81 (14th September 2020) - Reitz, Zachary L.; Butler, Alison
Abstract : Genome mining for VibH homologs reveals several Acinetobacter species with a gene cluster putatively encoding biosynthesis of catechol siderophores with an amine core. Enzyme flexibility allows for in vivo synthesis of non-native catechol compounds. Abstract : Genome mining for VibH homologs reveals several species of Acinetobacter with a gene cluster that putatively encodes the biosynthesis of catechol siderophores with an amine core. A. bouvetii DSM 14964 produces three novel biscatechol siderophores: propanochelin (1 ), butanochelin (2 ), and pentanochelin (3 ). This strain has a relaxed specificity for the amine substrate, allowing for the biosynthesis of a variety of non-natural siderophore analogs by precursor directed biosynthesis. Of potential synthetic utility, A. bouvetii DSM 14964 condenses 2, 3-dihydroxybenzoic acid (2, 3-DHB) to allylamine and propargylamine, producing catecholic compounds which bind iron(iii ) and may be further modified via thiol–ene or azide–alkyne click chemistry.